1999
DOI: 10.1083/jcb.145.7.1471
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Finger Protein A20 Inhibits TNF-induced NF-κB–dependent Gene Expression by Interfering with an RIP- or TRAF2-mediated Transactivation Signal and Directly Binds to a Novel NF-κB–inhibiting Protein ABIN

Abstract: The zinc finger protein A20 is a tumor necrosis factor (TNF)– and interleukin 1 (IL-1)-inducible protein that negatively regulates nuclear factor-kappa B (NF-κB)–dependent gene expression. However, the molecular mechanism by which A20 exerts this effect is still unclear. We show that A20 does not inhibit TNF- induced nuclear translocation and DNA binding of NF-κB, although it completely prevents the TNF- induced activation of an NF-κB–dependent reporter gene, as well as TNF-induced IL-6 and granulocyte macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
270
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(282 citation statements)
references
References 73 publications
(122 reference statements)
11
270
1
Order By: Relevance
“…We have already pointed out that ABIN proteins interfere with NF-kB signaling downstream of TRAF2/6, but upstream of IKKb (Heyninck et al, 1999;Van Huffel et al, 2001;Wullaert et al, 2007), and others showed that ABIN proteins can bind NEMO (Liu et al, 2004;Mauro et al, 2006;Weaver et al, 2007). Moreover, we here showed that both the UBAN domain and the NBD of ABIN-1 are involved in its NF-kB inhibitory function ( Figure 3c).…”
Section: Abin-1 Interacts With Ubiquitinated Nemosupporting
confidence: 63%
See 1 more Smart Citation
“…We have already pointed out that ABIN proteins interfere with NF-kB signaling downstream of TRAF2/6, but upstream of IKKb (Heyninck et al, 1999;Van Huffel et al, 2001;Wullaert et al, 2007), and others showed that ABIN proteins can bind NEMO (Liu et al, 2004;Mauro et al, 2006;Weaver et al, 2007). Moreover, we here showed that both the UBAN domain and the NBD of ABIN-1 are involved in its NF-kB inhibitory function ( Figure 3c).…”
Section: Abin-1 Interacts With Ubiquitinated Nemosupporting
confidence: 63%
“…The ABIN proteins were originally identified as three different intracellular NF-kB inhibitory proteins that bind the deubiquitinating protein A20 (Heyninck et al, 1999;Van Huffel et al, 2001;Wullaert et al, 2007). ABINs show partial sequence homology in a number of short regions, designated ABIN homology domains (AHDs).…”
mentioning
confidence: 99%
“…Two different splice variants of approximately 2800 and 2600 nucleotides long were found, containing open reading frames of respectively 1941 and 1792 nucleotides and encoding proteins of 72 and 68 kDa, respectively [9]. In contrast to the human ABIN-1 isoforms, the two murine splice variants differ at their N-terminus due to the initiation from two different methionines.…”
Section: Identification Of Abinsmentioning
confidence: 96%
“…Yeast two-hybrid screening of a mouse fibroblast L929r2 cDNA library with A20 as bait originally led to the identification of A20-binding inhibitor of NF-B (ABIN)-1 and ABIN-2 [9]. A TBLASTN search in the non-redundant and expressed sequence tag database identified ABIN-3 as another related protein [10].…”
Section: Identification Of Abinsmentioning
confidence: 99%
See 1 more Smart Citation